Post operative analgesia after caesarean section: an experience with intrathecal buprenorphine - Sunil Dixit (Indian Journal of Anaesthesia, 2007)
Buprenorphine is a mixed agonist-antagonist narcotic with high affinity at both µ and k opiate receptors. The aim of the study was to compare intrathecal bupivacaine (0.5%) and buprenorphine (60µg) with bupivacaine (0.5%) for postoperative analgesia in caesarean section. Sixty parturients undergoing elective lower segment caesarean section (LSCS) were randomly selected after dividing into two groups of 30 each. Control group (C) received 1.70ml (8.5mg) of bupivacaine (0.5%) while patients of Study group (S) received 1.70ml (8.5mg) bupivacaine 0.5% + 60µg buprenorphine. Onset of analgesia was 5.35± 1.79 min in Control group, while 1.85 ± 1.39 min in Study group (P< 0.001). The total duration of analgesia was prolonged from145.16 ± 25.86 min in Control group to 491.26 ± 153.97min in Study group. We conclude that intrathecal buprenorphine is a suitable drug for postoperative analgesia after caesarean section with no effects on neonatal Apgar scores with minimal side effects.